Chronic Disease of State Corporatism in Indonesian Village Government - Sri Wahyu Kridasakti; Mohamad Fadli; Abdul Madjid; Chanif Nurcholis (Faculty of Law, Sriwijaya University, Indonesia, 2022)
The institutional regulation of the Indonesian village government from the Dutch colonial era (1906) until the Reform Era has practically shown controversy of pros and cons. Through correct regulation, the village should be able to prosper. However, the applied regulation as a tool of social engineering during the inter-period has failed to bring the village to prosper. The legal gaps are whether the applied state-corporatism norms on Indonesia village regulation have met the principles of good local governance. This study aims to provide corrections to the heresy of legal construction of the village regulations. This legal method of study was a nomological type with a statute approach. The technical analysis used was content analysis. The results showed that the legality of the village government status, which is state-corporatism containing in norms of the provision of Number 1, Number 2, Number 7, Article 6 paragraph (1), Article 6 paragraph (1) of the Law 6/2014 is not synchronous vertically to the 1945 Constitution. The results of the legitimacy study also revealed that Articles 12, 19, 19 (b)(c)(d), 69 of Law 6/2014 concerning the Authority and Changes of the Status of Urban Villages (Gesellschaft) into Common-Village (gemeinschaft) implies horizontal disharmony to the Law 30/2014 concerning Government Administration. Therefore Law 6/2014 needs to be revoked and replaced with an organic law derived from Articles 18, 18A and 18B of the 1945 Indonesia Constitution.